Therapeutic Myeloperoxidase Inhibition Attenuates Neutrophil Activation, ANCA-Mediated Endothelial Damage, and Crescentic GN - Antonelou, Marilina (J Am Soc Nephrol, 2020)
BACKGROUND: Myeloperoxidase released after neutrophil and monocyte activation can generate reactive oxygen species, leading to host tissue damage. Extracellular glomerular myeloperoxidase deposition, seen in ANCA-associated vasculitis, may enhance crescentic GN through antigen-specific T and B cell activation. Myeloperoxidase-deficient animals have attenuated GN early on, but augmented T cell responses. We investigated the effect of myeloperoxidase inhibition, using the myeloperoxidase inhibitor AZM198, to understand its potential role in treating crescentic GN. METHODS: We evaluated renal biopsy samples from patients with various forms of crescentic GN for myeloperoxidase and neutrophils, measured serum myeloperoxidase concentration in patients with ANCA-associated vasculitis and controls, and assessed neutrophil extracellular trap formation, reactive oxygen species production, and neutrophil degranulation in ANCA-stimulated neutrophils in the absence and presence of AZM198. We also tested the effect of AZM198 on ANCA-stimulated neutrophil-mediated endothelial cell damage in vitro, as well as on crescentic GN severity and antigen-specific T cell reactivity in the murine model of nephrotoxic nephritis. RESULTS: All biopsy specimens with crescentic GN had extracellular glomerular myeloperoxidase deposition that correlated significantly with eGFR and crescent formation. In vitro, AZM198 led to a significant reduction in neutrophil extracellular trap formation, reactive oxygen species production, and released human neutrophil peptide levels, and attenuated neutrophil-mediated endothelial cell damage. In vivo, delayed AZM198 treatment significantly reduced proteinuria, glomerular thrombosis, serum creatinine, and glomerular macrophage infiltration, without increasing adaptive T cell responses. CONCLUSIONS: Myeloperoxidase inhibition reduced neutrophil degranulation and neutrophil-mediated endothelial cell damage in patients with ANCA-associated vasculitis. In preclinical crescentic GN, delayed myeloperoxidase inhibition suppressed kidney damage without augmenting adaptive immune responses, suggesting it might offer a novel adjunctive therapeutic approach in crescentic GN.